2003
DOI: 10.1002/ana.10795
|View full text |Cite
|
Sign up to set email alerts
|

The new mutation, E46K, of α‐synuclein causes parkinson and Lewy body dementia

Abstract: Familial parkinsonism and dementia with cortical and subcortical Lewy bodies is uncommon, and no genetic defect has been reported in the previously described sibships. We present a Spanish family with autosomal dominant parkinsonism, dementia, and visual hallucinations of variable severity. The postmortem examination showed atrophy of the substantia nigra, lack of Alzheimer pathology, and numerous Lewy bodies which were immunoreactive to alpha-synuclein and ubiquitin in cortical and subcortical areas. Sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
1,789
1
28

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,542 publications
(1,830 citation statements)
references
References 46 publications
12
1,789
1
28
Order By: Relevance
“…In addition, Gly111-Glu114 and Gly132 located in the C-terminal region present abundant 3 10 -helix formation (up to 28%) for both the wild-type and A30 mutant-type αS proteins. We also note a larger decrease in 3 10 -helix abundance (≥5%) at Phe94-Leu100 in the A30P mutant-type structures rather than those of the wild-type αS protein.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…In addition, Gly111-Glu114 and Gly132 located in the C-terminal region present abundant 3 10 -helix formation (up to 28%) for both the wild-type and A30 mutant-type αS proteins. We also note a larger decrease in 3 10 -helix abundance (≥5%) at Phe94-Leu100 in the A30P mutant-type structures rather than those of the wild-type αS protein.…”
mentioning
confidence: 64%
“…Interestingly, Gly7-Glu13, Val15-Ala17, Lys32-Val40, and Lys43-Gly47 adopt more prominent helical structure (α-helix or 3 10 -helix; up to 30%) in the structures of the A30P mutanttype than in those of the wild-type αS protein. In contrast, the α-helix and 3 10 -helix contents at Gly25-Lys32 in the wild-type αS protein structures decrease or disappear upon A30P mutation. This finding is in agreement with the NMR measurements that reported reduced helical propensity for Ala18-Gly31 upon A30P mutation.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Mis‐sense mutations13, 36, 37, 38, 39, 40 and duplications or triplications of the SNCA gene, which encodes αS, lead to autosomal dominant early onset PD 41, 42. It has previously been shown that the formation of αS oligomers in vitro is concentration dependent,12 and ADPAINT now enables us to determine whether this dependence is reflected in cellular models that overexpress αS.…”
mentioning
confidence: 99%